KEY ETHICAL CHALLENGES OF THE TOTAL DEFENCE CONCEPT IMPLEMENTATION IN THE REPUBLIC OF SERBIA - Stanar, Dragan (Srpska politička misao, 2026)
The author analyses the key ethical challenges of implementing the concept of total defense in the Republic of Serbia, starting from the assumption that normatively unresolved dilemmas may undermine its functional and moral sustainability. After conceptually defining total defense as a model that entails the comprehensive participation of all societal actors in the defense of the state, the author examines three central ethical issues: the ethical nature and grounding of the duty to participate in defense, the implications of fulfilling this duty during armed conflict, and the question of responsibility for failing to fulfil it. The duty of defense is interpreted as an imperative arising from the very ontology of the state and collective freedom, rather than as a matter of voluntariness. At the same time, attention is drawn to the challenges of its internalization within the context of a contemporary “rights-based society.” Particular focus is given to the problem of crossing the threshold of “direct participation in hostilities,” which may result in the loss of civilian immunity and the blurring of the distinction between legitimate and illegitimate targets, especially under the conditions of modern warfare. Finally, the author analyses the issue of legal and moral responsibility for the failure to fulfil this duty, warning of the dangers of arbitrary and ideologically motivated post-war sanctions. The conclusion is that the optimal implementation of the concept of total defense requires precise normative regulation, clearly defined limits of duty, and proportionate sanctions, in order for the concept to be not only effective, but also morally legitimate and sustainable in the long term.
Keywords: total defence concept; duty; responsibility; moral; ethics; war; collaboration; legitimacy of targets